Ionic liquid-based microwave-assisted extraction of lipid and eicosapentaenoic acid from Nannochloropsis oceanica biomass: experimental optimization approach - Motlagh, Shiva Rezaei; Harun, Razif; Awang Biak, Dayang Radiah; Hussain, Siti Aslina; Omar, Rozita; Khezri, Ramin; Elgharbawy, Amal A. (Springer Netherlands, 2021)
Lipids and eicosapentaenoic acid (EPA) compounds from Nannochloropsis oceanica biomass were extracted using a combination of ionic liquids (ILs) and microwave-assisted extraction (MAE). When compared to conventional Soxhlet extraction, the proposed novel approach in this paper successfully improved both the yield of total extracted lipids and the EPA content. The effect of selected extraction parameters including the weight of applied IL (tetramethyl ammonium chloride: [TMAm][Cl]) (0.5–2.5 g), reaction temperature (60–100 °C), and process time (5–30 min) on final products was evaluated using response surface methodology (RSM). The optimal values of parameters were determined and three-dimensional response surfaces were plotted from the mathematical models and discussed. The yield of total extracted lipids and the content of EPA were found 19.58 wt% (g g−1 of total biomass) and 37.919 mg g−1 of total FAME respectively, when the extraction process was accomplished in 24.69 min at 88.18 °C and with 1.65 g of ILs. Analysis of variance (ANOVA) was applied in the analysis of experimental data and the R2 of 0.9506 and 0.9517 for total lipid and EPA models, respectively, show that the experimental findings were well aligned with the predicted values. Furthermore, at similar condition, the extraction process was replicated using two other types of ILs namely [EMIM][Cl] and [EMPyrro][Br] to extract the total lipid and EPA. The results showed that [TMAm][Cl] performed better in extracting compounds from microalgae. Based on the findings, this study shows that the combination of ILs mediated in water-based MAE is an environmentally friendly, reliable, and efficacious approach to enhance the extraction of lipids and EPA from N. oceanica with considerable potential to be up-scaled for commercial applications.